2023
DOI: 10.3390/ijms24043731
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Product of Peroxy Radical Self-Reaction Probed with VUV Photoionization Mass Spectrometry and Theoretical Calculations: The Case of C2H5OOC2H5

Abstract: Organic peroxy radicals (RO2) as key intermediates in tropospheric chemistry exert a controlling influence on the cycling of atmospheric reactive radicals and the production of secondary pollutants, such as ozone and secondary organic aerosols (SOA). Herein, we present a comprehensive study of the self-reaction of ethyl peroxy radicals (C2H5O2) by using advanced vacuum ultraviolet (VUV) photoionization mass spectrometry in combination with theoretical calculations. A VUV discharge lamp in Hefei and synchrotron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Such wall loss likely limited the ability of Barnes et al 14 to observe the ROOR. Additionally, a recent study published on the reactions of ethyl peroxy radicals 12 found a branching ratio to the accretion product of 10±5%, demonstrating that formation of the accretion product is significant even in small unsubstituted peroxy radical systems, lending further support to our results.…”
Section: Comparison With Earlier Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…Such wall loss likely limited the ability of Barnes et al 14 to observe the ROOR. Additionally, a recent study published on the reactions of ethyl peroxy radicals 12 found a branching ratio to the accretion product of 10±5%, demonstrating that formation of the accretion product is significant even in small unsubstituted peroxy radical systems, lending further support to our results.…”
Section: Comparison With Earlier Studiessupporting
confidence: 89%
“…17 The fraction of thermalized alkoxy radicals generated in Reaction (4) may differ from that generated by the reaction between RO 2 and NOc. The analysis of our data, as presented in ESI Appendix C, † indicates that approximately 20% of the alkoxy radicals in our system react with O 2 , whereas 29% of the alkoxy radicals in the system studied by Orlando et al react with O 2 at 298 K. While this As described above, in the limit where F external / 0, Q (eqn (11)) is a measure of the ratio of the radical propagating channels to the radical terminating channels of Reaction (4). In the limit where all HO 2 is produced internally to Reaction (4), >90% of the HO 2 reacts with HOCH 2 CH 2 OOc, and there are no secondary losses,…”
Section: Glycolaldehyde Formationsupporting
confidence: 49%
See 1 more Smart Citation
“…The decomposition of such dimer on reactor walls could lead to formation of aldehydes and thus appear as additional radical formation when measuring stable end products. The dimeric product has very recently been detected in the self-reaction of C 2 H 5 O 2 25 using advanced vacuum ultraviolet (VUV) photoionization mass spectrometry with a yield of 10 AE 5%. The dimer has also been directly detected by CIMS with a yield of 23% in the self-reaction of HOC 2 H 4 O 2 radicals and has been proven to decompose easily on quartz or metal surfaces.…”
Section: Determination Of Branching Ratiomentioning
confidence: 99%
“…Methane and ethane are amongst the most abundant hydrocarbons, and their atmospheric oxidation leads to the formation of methyl peroxy (CH 3 O 2 ) and ethyl peroxy (C 2 H 5 O 2 ) radicals. For both radicals, the kinetic and product distribution for the self-reaction has been studied numerous times (for CH 3 O 2 4–12 and for C 2 H 5 O 2 13–26 ), the same is true for their reaction with HO 2 (for CH 3 O 2 5,9,27–32 and for C 2 H 5 O 2 13,14,20,26,30,33–35 ). Their reaction with OH radicals has been the subject of a few studies (for CH 3 O 2 3,36–41 and for C 2 H 5 O 2 42–44 ).…”
Section: Introductionmentioning
confidence: 96%